2019
DOI: 10.3390/molecules24132359
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Profile of Elderberry Juice: A Natural-Based Bioactive Colouring Ingredient with Potential Food Application

Abstract: Elderberry (Sambucus nigra L.) is a widely disseminated plant that produces bright black berries containing high quantities of anthocyanins, acknowledged for their bioactivity and dye capacity. Besides other applications, anthocyanins might be employed as natural colouring agents to reduce/eliminate the use of artificial dyes, while providing positive effects on consumers’ health. Herein, the anthocyanins profile of elderberry juice was characterised by HPLC-DAD-ESI/MSn. In addition, its antioxidant capacity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…In contrast, elderberry puree contained anthocyanins and rutin as the major polyphenols. The same was stated by Da Silva et al [ 8 ], who identified cyanidin-3- O -sambubioside, cyanidin-3- O -glucoside, and cyanidin-3- O -sambubioside-5- O -glucoside as the most abundant anthocyanins in elderberry juice, and the study of Domínguez et al [ 10 ], who reported that rutin and, to a lesser extent, quercetin were the main representatives of the flavonoids group in the elderberries. Cosmulescu et al [ 29 ] identified five flavonoids and 10 phenolic acids in the fruit extract of wild-grown blackthorn.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In contrast, elderberry puree contained anthocyanins and rutin as the major polyphenols. The same was stated by Da Silva et al [ 8 ], who identified cyanidin-3- O -sambubioside, cyanidin-3- O -glucoside, and cyanidin-3- O -sambubioside-5- O -glucoside as the most abundant anthocyanins in elderberry juice, and the study of Domínguez et al [ 10 ], who reported that rutin and, to a lesser extent, quercetin were the main representatives of the flavonoids group in the elderberries. Cosmulescu et al [ 29 ] identified five flavonoids and 10 phenolic acids in the fruit extract of wild-grown blackthorn.…”
Section: Discussionsupporting
confidence: 76%
“…Elderberry, however, is added to yoghurt, but only in small concentrations, in order to enhance the dark reddish-violet color of, e.g., blueberry or forest fruit yoghurt, not as flavoring or a bioactive ingredient itself. Elderberry, the fruit of black elder ( Sambucus nigra L.) shrub, and its preparations (powders, extracts, concentrates) are used as a potent source of natural colorants because they contain considerable amounts of anthocyanins, mainly cyanidin glycosides [ 8 , 9 ]. Moreover, anthocyanins and other phenolic compounds, such as flavonols and phenolic acids from elderberries, are known for their excellent free-radical-scavenging ability [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stability of acylated anthocyanins depends on the types, numbers and positions of acyl groups, and aromatic acyl groups confer much greater stability than aliphatic ones by forming intramolecular co-pigment complexes (Zhao et al, 2017). In our experiments, the R4G anthocyanins were much more stable over time than enocyanins (from redskinned grapes) and elderberry anthocyanins, reflecting the higher content of acylated anthocyanins in the R4G extract but the prevalence of non-acylated anthocyanins in elderberries and grapes (Anesi et al, 2015;Da Silva et al, 2019). Surprisingly, the anthocyanins in the R4G extract were also more stable than natural red carrot anthocyanins.…”
Section: Discussionmentioning
confidence: 56%
“…Similar results were determined for croissants fortified with 4% elderberry juice. The product provided the same benefits compared to those with the addition of black carrot commercial dye [ 41 ].…”
Section: Resultsmentioning
confidence: 99%